Measuring circularity: An application of modified Material Circularity Indicator to agricultural systems - L. Rocchi; L. Paolotti; C. Cortina; F. F. Fagioli; Antonio Boggia (Agricultural and Food Economics, 2021)
The transition from a linear to a circular economy is a research trend topic, as well as the possibility to measure the degree of circularity of products and systems. In a linear economy, raw materials are taken from nature and transformed into final products, which are subsequently used and become waste. On the contrary, a circular economy is an economic model that is restorative by intent and design. To measure the degree of circularity is fundamental for understanding processes and improving them. Moreover, this kind of measure could be useful for driving policies on the topic and achieving a higher level of sustainability. Until now, only few studies have been focusing on how to effectively measure the circularity level of a product, a supply chain, or a service. Moreover, in the circular economy paradigm, there are two types of cycles: the technical and biological ones. Biological cycles are mainly connected to the agricultural sector, and for this kind of cycle, the lack of measurement is even bigger. However, some agricultural productions, such as intensive meat production processes, have basically a linear structure. Intensive broiler production, for instance, uses a quite high rate of inputs, which is not entirely converted into edible products but instead results in a percentage of wasteful outputs. The aim of this work is to propose a modification of one of the few available tools for measuring the circularity, the Material Circularity Indicator (MCI), for adapting it to biological cycles. The modified MCI was applied to the poultry sector, integrating the results with the Life Cycle Assessment methodology.
Keywords: 330; Broiler production system; Circular economy; Indicators; Life Cycle Assessment; Modified Material Circularity Indicator